Isoscaling: Geometry, correlations and symmetry energy - Dorso, Claudio Oscar (2006)
This work uses a simple model to understand the properties of isoscaling. Using a generalized percolation model, it is first shown that isoscaling is a general property of fragmenting systems. In particular, it is found that the usual isoscaling property can be seen as a limit case of bond percolation in lattices in D dimensions, with N colors, with independent probabilities for each color, and for any regular topology. The effect of introducing correlations is also studied. © 2006 The American Physical Society.